Lineamientos de seguridad vial para la prevención de la accidentalidad vial en los corredores del sistema integrado de transporte público (SITP). Caso de estudio: corredor de la avenida calle 72 (2018)
In Colombia, traffic accidents are the second cause of violent deaths. Therefore, the objective of the present investigation is to establish guidelines for the prevention of road traffic accidents and find their causes in the SITP corridors. The system has about 6500 vehicles (not including information from the provisional SITP) and ten assigned areas, but in this work only the road accident rate of the vehicles associated with the SITP was studied, based on the five pillars of the National Road Safety Plan . To this end, heat maps of the traffic accidents corresponding to the vehicles associated with the Engativá area were made from 2012 to June of the year 2017, which allowed determining the areas of greatest accident and the distances from the event to the nearest bus stop. From the areas of greatest accident, records were selected for the analysis based on the Haddon matrix, and subsequently the analysis, data processing and generation of the final report were made. Once processed and refined, the data was uploaded to TransCAD, heat maps were created associating events to the nearest arc of the transport network and then a density map was generated. In order to corroborate the trend of the information, maps were created per year that showed the behavior of the accident and possible risk zones. From the previous processing, seven risk sectors emerged, of which Sector 4 was selected with 366 events located on 72nd Avenue, between Ciudad de Cali Avenue (Carrera 86) and Boyacá Avenue (Carrera 72). From the calculation of the theoretical sample we have: N = 368. The sector that fits most is number 4, with 366 events. As a null hypothesis, it is stated that more than 50% of accident events occur at a distance less than or equal to 40 meters from the whereabouts, due to poor infrastructure in whereabouts; as alternative hypothesis is that less than 50% of the accident events are generated at a distance less than or equal to 40 meters from the whereabouts due to poor infrastructure in whereabouts, obtaining critical value: Zc = -1.64 and test value: Zp = 2.30; alternative hypothesis is rejected and null hypothesis is accepted. From the above, road safety guidelines for the prevention of accidents in the SITP corridors are proposed.